The Effect Institutional Ownership and Environmental Certification on Carbon Emissions Disclosure - Abdul Ghofur; Mohammad Syafik (Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores carbon emission disclosure by non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2022 period. The purpose of this study is to analyze the effect of institutional ownership on the intensity of carbon emission disclosure, as well as the moderating role of environmental certifications such as ISO 14001 or EMAS in this relationship. The method used is quantitative analysis through unbalanced panel data regression with a fixed effects model, including variables such as institutional ownership, environmental certification, and their interaction. The results of the analysis show that institutional ownership significantly increases the level of carbon emission disclosure, as oversight pressure from large shareholders encourages managerial transparency. However, companies with environmental certification tend to reduce additional disclosure, as if they already feel they have met credibility standards. This is evident from the negative interaction coefficient between institutional ownership and environmental certification. This finding reveals a paradox: certification, which should increase environmental responsibility, can reduce the initiative to share information voluntarily. In conclusion, regulators and institutional stakeholders need to promote policies that ensure consistent emissions disclosure, including among certified companies, to reduce information asymmetry and strengthen carbon accountability.